2021
DOI: 10.1002/pon.5812
|View full text |Cite
|
Sign up to set email alerts
|

Decisional capacity determination and serious mental illness in oncology: Implications for equitable and beneficent care

Abstract: Background: Patients with Serious Mental Illness (SMI) have worse survival compared to cancer patients without SMI after controlling for delayed diagnosis.Decision-making capacity (DMC) may be impaired in both populations (cancer or SMI). DMC may be further impaired based on coupled vulnerability factors that challenge Shared Decision Making (SDM) for patients with cancer and SMI.Methods: Psychiatric consultations for DMC in hospitalized patients with cancer (n = 97) were consecutively evaluated across a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The study found that there were barriers to cancer care provision for patients affected by SMI: fragmentation of care; healthcare providers' understanding of SMI; complex nature of presentation; and specialized care needs. In a Japanese study, by analyzing the responses of 439 professionals, Etoh et al 23 A very specific and important point was raised by McFarland et al 25 in the USA. In a series of psychiatric consultations for patients with SMI and cancer, they found that shared decision making was often a problem.…”
Section: Stigma Marginalization and Communication Problemsmentioning
confidence: 99%
“…The study found that there were barriers to cancer care provision for patients affected by SMI: fragmentation of care; healthcare providers' understanding of SMI; complex nature of presentation; and specialized care needs. In a Japanese study, by analyzing the responses of 439 professionals, Etoh et al 23 A very specific and important point was raised by McFarland et al 25 in the USA. In a series of psychiatric consultations for patients with SMI and cancer, they found that shared decision making was often a problem.…”
Section: Stigma Marginalization and Communication Problemsmentioning
confidence: 99%